2013
DOI: 10.1073/pnas.1315292110
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking ANGPTL8 (Betatrophin) manifest disrupted triglyceride metabolism without impaired glucose homeostasis

Abstract: Angiopoietin-like protein (ANGPTL)8 (alternatively called TD26, RIFL, Lipasin, and Betatrophin) is a newly recognized ANGPTL family member that has been implicated in both triglyceride (TG) and glucose metabolism. Hepatic overexpression of ANGPTL8 causes hypertriglyceridemia and increased insulin secretion. Here we examined the effects of inactivating Angptl8 on TG and glucose metabolism in mice. Angptl8 knockout (Angptl8 −/− ) mice gained weight more slowly than wild-type littermates due to a selective reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
358
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(395 citation statements)
references
References 39 publications
28
358
9
Order By: Relevance
“…Mice lacking betatrophin had a 70% reduction in plasma triglyceride levels compared with littermate control subjects (23). Adenovirus-mediated hepatic overexpression of betatrophin increased plasma triglyceride levels more than five-fold (24).…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking betatrophin had a 70% reduction in plasma triglyceride levels compared with littermate control subjects (23). Adenovirus-mediated hepatic overexpression of betatrophin increased plasma triglyceride levels more than five-fold (24).…”
Section: Discussionmentioning
confidence: 99%
“…Fenzl et al showed that betatrophin was associated with plasma atherogenic lipids in obesity and type 2 diabetes, and not associated with beta cell function and glucose homeostasis [9]. In Angptl8 (betatrophin) knockout mice, serum TG was reduced after refeeding and low TG was associated with reduced very low density lipoprotein secretion and increased LPL activity, but not with glucose impairment in glucose tolerance tests [18]. Betatrophin (Angptl8) inhibits LPL activity directly or indirectly by promoting Angptl3 cleavage, since cleavage of Angptl3 inhibits LPL activity directly [19][20][21][22].…”
Section: Disclosurementioning
confidence: 99%
“…Under circumstances favouring FA deposition as TGs in WAT, it is plausible that hydrolysis of the stored TGs should simultaneously be suppressed. It thus seems that, analogous to the activity of Angptl8 as an inhibitor of lipolysis in the circulation (Quagliarini et al, 2012;Wang et al, 2013), it could execute a similar function intracellularly. We failed to detect changes in the mRNA expression of central mediators of lipolysis, ATGL and HSL, while a small increase of the Angptl4 message was evident; Angptl4 acts as stimulator of adipocyte lipolysis (Gray et al, 2012), so its induction could contribute to the observed increase of lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Since we saw in the Angptl8 KD adipocytes a reduction of stored TGs and because Angptl8 together with Angptl3 inhibits LPL activity in the circulation (Quagliarini et al, 2012;Wang et al, 2013), we decided to measure the intracellular lipolysis in the Angptl8 and control adipocytes in the presence or absence of b-adrenergic (isoproterenol) stimulation. Measurement of NEFA released into the culture medium revealed a significant enhancement of lipolysis in both KD1 and KD2 cell pools as compared to the non-targeting control, the volume of the effect being more pronounced for KD1.…”
Section: Knock-down Of Angptl8 Reduces Ether Phospholipids As Well Asmentioning
confidence: 99%
See 1 more Smart Citation